Historicist study of“Mufti” in Early Modern English [Early English Book Online – Text Creation Partnership (EEBO-TCP)] - Nabi, Taj (JELLL, 2023)
This research makes historicist study of the word mufti in the early modern English studies while exploring the catalogue of Early English Books Online Text Creation Partnership (EEBO-TCP). The study also focuses on the spelling variations, evolution, symbolic meanings, connotations, denotations, anglicization, association, construction and (mis) representation of the term during the period starting from 1499 (first usage of the term) till 1650. For this purpose, the research has been delimited to the Word Index (Phase-I) of the EEBO-TCP. However, the entire record found in Phase-I consisted of 949 matches in 171 records with variation in spelling and frequency of the term: mufte (1), muftee(41), muf∣tee(2), muftees (12), muf∣tees(1), muftell(1), muter (1), mufti (790), muf∣ti(13), mufti▪(1), muftie(21), muftie’s(1), muftis (33), muf∣ties(1), mufties-moore(1), mufti's (23), muftis (1), muftiship (2). It was not possible to carry out research on all matches and records of Phase I due to time constraints. Therefore, the research focuses on the first 150 years, i.e., 1500 to 1650 published online works available in the database. The catalogue corpus has found 39 records and more than 200 matches of the term(s) during the mentioned period of the understudy research. The study has found that the word Mufti (with mentioned spelling variations) has often been used in historical and contextual paradigms from the perspectives of Western writers mostly during the East-West, Anglo-Ottoman, Anglo-African, Anglo-Persian and Anglo-Asian encounters. The word has time and again explained in the Christian religious context for readers of the Western world as Chief Priest, High Priest, High Bishop, Chief of Religion, Archpriest, Archbishop and Powerful Figure who had the power of presentation and persuasion. The research has also found that during the mentioned period Mufti had a dominant position with multiple roles and responsibilities: interpreting laws and complex issues as legal expert, issuing decrees in light of the religious laws, leading religious rituals, and rendering religious education to students in the seminaries. Throughout the Islamic history, the trained and well qualified Mufti, the capable Jurist and Islamic legal authority, used to give an authoritative and formal opinion (fatwa) in answer to an inquiry based in Islamic Sharia principles and precedents. It used to be compiled in legal reference manuals for record. The study has also found that the meaning of the word has undergone drastic change later in the 19th century during the British colonial experience of India. The term once used for the high position of Islamic scholar and Jurist (Mufti) has been turned into somewhat funny connotation of a slang and degraded word for casual dress, leisure and off-duty time for the uniformed personnel.